PERAWATAN SERTA PEMANENAN DAN APLIKASI VERMIKOMPOS BERBAHAN DASAR PELEPAH KELAPA SAWIT DI KAMPUNG SIALANG SAKTI, KABUPATEN SIAK - Besri Nasrul; Nursiani Lubis; Irwin Mirza Umami; Yunandra Yunandra; Tito Handoko; Rizqy Ridho Prakasa; Rezi Abdurrahman (Jurnal Hilirisasi IPTEKS, 2025)
This community service program aimed to empower oil palm farmers in Sialang Sakti Village, Siak Regency, by utilizing oil palm fronds as raw material for vermicompost production to support sustainable agriculture and the implementation of the Indonesian Sustainable Palm Oil (ISPO) standards. The main problem faced by the partner group was the accumulation of unutilized frond waste and the farmers’ limited knowledge of organic waste management. The program was conducted from July 27 to August 23, 2024, involving members of the Manunggal Sakti Farmers Group and student volunteers. The activities included socialization, technical training on vermicomposting, media maintenance and observation, harvesting and packaging of vermicompost, and field application on oil palm plantations. Data were collected through direct observation, laboratory analysis, and community satisfaction surveys conducted before and after the program using questionnaires. The results indicated a significant improvement in farmers’ knowledge and skills in producing and applying vermicompost. The final product exhibited desirable characteristics dark color, earthy odor, crumbly texture, and nutrient content meeting organic fertilizer standards. The program generated direct benefits by reducing palm frond waste and enhancing farmers’ awareness of organic waste utilization. In conclusion, the program successfully achieved its objectives in empowering the local community and improving waste management capacity. Although challenges such as limited time and production facilities were encountered, the strong enthusiasm of participants ensured the program’s sustainability through plans to establish a farmer-based vermicompost business unit.